Mechanical energy comparison of V1 and V2 skating - Smith, G.; Toftegaard, Ø.; Reid, R. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: The various skating techniques in skiing are sometimes described as similar to gearing systems in cycling where terrain influences the choice of gear. Skating uphill, many skiers use V2 technique on low angled slopes and V1 on steeper hills. Treadmill testing of skating has compared V1 and V2 techniques for various physiological charact-eristics (Kvamme et al., 2005) but measurements on snow are more difficult. Limited energy analysis of classical skiing is available (Pellegrini et al. 2013) but none has been reported for skating. In this paper, world cup racers were analyzed using 3D video techniques on a long climb where both V1 and V2 techniques were used by some skiers.